Polygenic risk scores for prediction of breast cancer risk in women of African ancestry: a cross-ancestry approach. Issue 18 (12th May 2022) - Gao, Guimin; Zhao, Fangyuan; Ahearn, Thomas U; Lunetta, Kathryn L; Troester, Melissa A; Du, Zhaohui; Ogundiran, Temidayo O; Ojengbede, Oladosu; Blot, William; Nathanson, Katherine L; Domchek, Susan M; Nemesure, Barbara; et al.
Abstract: Polygenic risk scores (PRSs) are useful for predicting breast cancer risk, but the prediction accuracy of existing PRSs in women of African ancestry (AA) remains relatively low. We aim to develop optimal PRSs for the prediction of overall and estrogen receptor (ER) subtype-specific breast cancer risk in AA women. The AA dataset comprised 9235 cases and 10 184 controls from four genome-wide association study (GWAS) consortia and a GWAS study in Ghana. We randomly divided samples into training and validation sets. We built PRSs using individual-level AA data by a forward stepwise logistic regression and then developed joint PRSs that combined (1) the PRSs built in the AA training dataset and (2) a 313-variant PRS previously developed in women of European ancestry. PRSs were evaluated in the AA validation set. For overall breast cancer, the odds ratio per standard deviation of the joint PRS in the validation set was 1.34 [95% confidence interval (CI): 1.27–1.42] with the area under receiver operating characteristic curve (AUC) of 0.581. Compared with women with average risk (40th–60th PRS percentile), women in the top decile of the PRS had a 1.98-fold increased risk (95% CI: 1.63–2.39). For PRSs of ER-positive and ER-negative breast cancer, the AUCs were 0.608 and 0.576, respectively. Compared with existing methods, the proposed joint PRSs can improve prediction of breast cancer risk in AA women.